2021
DOI: 10.1111/jora.12610
|View full text |Cite
|
Sign up to set email alerts
|

Weighing the Risk: Developmental Pathways and Processes Underlying Obesity to Substance Use in Adolescence

Abstract: Research on co‐occurring obesity and substance use in adolescence has grown substantially in the past decade, but questions on the pathways and processes underlying co‐occurrence remain. This review first synthesizes empirical findings on the relationship between obesity and substance use (e.g., alcohol, cannabis, tobacco use). Multidisciplinary theoretical frameworks referencing behavioral medicine, neuroscience, psychology, and public health are then used to inform an interdisciplinary, conceptual model focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 135 publications
0
2
0
Order By: Relevance
“…In a meta-analysis of 21 studies, active smoking increased the risk of childhood obesity by 17%. In a bidirectional analysis of the correlation between BMI and smoking, a higher BMI did not predict an increased risk for cigarette smoking, while cigarette smoking predicted a higher BMI, and higher frequency of cigarette smoking in adolescence predicted chronic obesity in young adulthood (37)(38)(39). Given the demonstrated correlation between e-cigarette use and cigarette smoking among adolescents, the association between obesity and cigarette smoking could also apply to e-cigarette use (40).…”
Section: Smoking Alcohol and Drugsmentioning
confidence: 99%
“…In a meta-analysis of 21 studies, active smoking increased the risk of childhood obesity by 17%. In a bidirectional analysis of the correlation between BMI and smoking, a higher BMI did not predict an increased risk for cigarette smoking, while cigarette smoking predicted a higher BMI, and higher frequency of cigarette smoking in adolescence predicted chronic obesity in young adulthood (37)(38)(39). Given the demonstrated correlation between e-cigarette use and cigarette smoking among adolescents, the association between obesity and cigarette smoking could also apply to e-cigarette use (40).…”
Section: Smoking Alcohol and Drugsmentioning
confidence: 99%
“…Mason et al [ 2 ] found that about one in seven adolescents aged 12 to 18 in the United States (U.S.) have engaged in alcohol use at some point in their lives. In a longitudinal study following adolescents into adulthood, it was found that heavy drinkers were more likely to be obese in young adulthood, and obese adolescents had a higher prevalence of early alcohol use when compared to adolescents who were not obese [ 3 ]. While the intersection of these two public health issues has been studied previously [ 4 7 ], few studies have examined how the intersection of these issues differs between adolescents from urban and rural localities in the U.S. A study now two decades-old found high rates of alcohol usage among adolescents both in rural and urban areas, although, those in rural areas had a higher usage and higher prevalence of being overweight or obese than adolescents living in urban or suburban areas [ 8 ].…”
Section: Introductionmentioning
confidence: 99%